Sandbar shark aggregation in the central Mediterranean Sea and potential effects of tourism. Issue 6 (10th January 2021) - Cattano, C.; Turco, G.; Di Lorenzo, M.; Gristina, M.; Visconti, G.; Milazzo, M.
Abstract: An aggregation of sandbar sharks Carcharhinus plumbeus occurs every summer around the remote uninhabited islet of Lampione (Pelagie Islands Marine Protected Area, south‐western Mediterranean Sea), attracting an increasing number of tourists for a shark watching experience. Despite the ecological and socio‐economic importance of this rare occurrence in Mediterranean waters, there is a lack of scientific data and lack of information as to the potential impact of tourist activities on the presence and behaviour of this shark species. Using baited underwater videos, this study provides the first assessment of this shark aggregation, as well as a preliminary evaluation of the potential effects that boating and diving activities may have on sandbar sharks during two different periods within the tourism season (July and September 2019). Overall, 241 sandbar shark sightings (with up to five individuals together) were recorded in July, whereas there were only six sightings in September. The average MaxN was 1.18 hr −1 (±0.21 hr −1 SE) and 0.22 hr −1 (±0.10 hr −1 SE) individuals in July and September respectively. Higher frequentation levels of divers and boats significantly reduced the number of shark sightings at the aggregation site. This study emphasizes the need for further investigations on Mediterranean shark aggregations and the implementation of specific conservation measures, such as an increase of protection level in Lampione and better enforcement, aside from strategies that promote sustainable tourism, including restrictions on the number of boats and divers' visits per day. In the meantime, a precautionary approach aimed at regulating the interactions between tourists and sharks should be implemented through the application of a self‐regulatory code of conduct for divers when sharks aggregate around the island.